Karakteristik demografi dan alasan motivasional pilihan karir pendaftar TNI AL strata perwira, bintara, dan tamtama - Mithra; Marwanto, Tri Budi; Satriyo, Marcellinus Agung (Jurnal Psikologi Poseidon, 2025)
This exploratory study aims to identify preliminary indications of the relationship between demographic aspects and career choice motives among Indonesian Navy applicants. Data were obtained from secondary sources in the form of 2023 biodata records and analyzed using descriptive statistics. The respondents consisted of 1,206 prospective servicemen from various entry levels, selected through stratified purposive sampling. Demographic variables included age, gender, education, domicile, family background, and previous selection experience. Findings in these research are: Among cadet candidates, six main themes emerged: “personal aspiration,” “serving the nation,” “family pride,” “leadership,” “world exploration,” and “employment need.” For non-commissioned officer candidates, male applicants preferred operational duties aboard warships or within the Marine Corps, whereas female applicants tended to choose administrative roles. Only family background showed a strong indication related to career choice. The selection ratio, especially among female NCO applicants, was low. The large gap between applicants and available quotas may lead to recurring applicants or repeated failures, potentially resulting in frustration and apathy. The integrated recruitment system of TNI (Army, Navy, and Air Force) for the officer level, introduced in 2024, might be expected to mitigate potential issues caused by the low selection ratio.